(untitled) (Scientific journal of the Fergana State University, 2025)
This article primarily discusses the development of life skills and career guidance for students through the teaching of foreign languages in non-state educational institutions. Nowadays, career guidance of young people has become one of the urgent issues, since most educational institutions emphasize the development of intellectual knowledge of students, but the skills necessary for professional activity are neglected. Therefore, this article shows the need to effectively implement the methodology of teaching life skills in the education system of Uzbekistan. Considering that non-state educational institutions and training centers cover a large number of young people, it is essential to integrate life skills into the training programs of these centers. This article discusses the issues of reforming the education provided in existing non-state educational institutions in Uzbekistan, bringing it to a new level, applying innovative methodologies recognized worldwide, and thereby directing them to future professions.